The macroeconomic effects of debt relief policies during recessions - Soyoung Lee (Bank of Canada, 2023)
I study debt relief as a stimulus policy using a dynamic stochastic general equilibrium model that captures the rich heterogeneity in households' balance sheets. In this environment, a large-scale mortgage principal reduction can amplify a recovery, support house prices and lower foreclosures. The nature of the intervention, in terms of its eligibility, liquidity and financing, shapes its macroeconomic impact. This impact rests on how resources are redistributed across households that vary in their marginal propensities to consume. The availability of bankruptcy on unsecured debt quantitatively changes the macroeconomic response to large-scale mortgage relief by reducing precautionary savings.
Keywords: E21; E32; E6; 330; Business fluctuations and cycles; Debt management; Housing; Credit and creditaggregates